A Reconsideration of Hofstede's Fifth Dimension: New Flexibility Versus Monumentalism Data From 54 Countries. (July 2018) - Minkov, Michael; Bond, Michael H.; Dutt, Pinaki; Schachner, Michael; Morales, Oswaldo; Sanchez, Carlos; Jandosova, Janar; Khassenbekov, Yerlan; Mudd, Ben
Hofstede's "long-term orientation" (LTO) may be one of the most important dimensions of national culture, as it highlights differences on a continuum from East Asia to Africa and Latin America, strongly associated with differences in educational achievement. However, LTO's structure lacks theoretical coherence. We show that a statistically similar, and theoretically more focused and coherent, dimension of national culture, called "flexibility versus monumentalism, " or vice versa, can be extracted from national differences in self-enhancement and self-stability or self-consistency, as well as a willingness to help people. Using data from nearly 53, 000 respondents recruited probabilistically from 54 countries, we provide a new national flexibility-versus-monumentalism index that measures key cultural differences on the world's East–West geographic axis and predicts educational achievement better than LTO or any other known dimension of national culture.